The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s40264-015-0281-0
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Adverse Drug Reactions in Europe: A Review of Recent Observational Studies

Abstract: Adverse drug reactions (ADRs) cause considerable mortality and morbidity but no recent reviews are currently available for the European region. Therefore, we performed a review of all epidemiological studies quantifying ADRs in a European setting that were published between 1 January 2000 and 3 September 2014. Included studies assessed the number of patients who were admitted to hospital due to an ADR, studies that assessed the number of patients who developed an ADR during hospitalization, and studies that me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

18
275
1
34

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 352 publications
(328 citation statements)
references
References 61 publications
18
275
1
34
Order By: Relevance
“…This finding is broadly compatible with pooled data from older studies, and with other similar studies [2][3][4][5]. A recent review on the epidemiology of ADRs in Europe found that 3.5% of hospital admissions were due to ADRs [6]. An observational study aimed at measuring the burden of ADRs in medical wards of four hospitals conducted in South Africa also found 8.4% ADR related hospital admissions [7].…”
Section: Introductionsupporting
confidence: 87%
“…This finding is broadly compatible with pooled data from older studies, and with other similar studies [2][3][4][5]. A recent review on the epidemiology of ADRs in Europe found that 3.5% of hospital admissions were due to ADRs [6]. An observational study aimed at measuring the burden of ADRs in medical wards of four hospitals conducted in South Africa also found 8.4% ADR related hospital admissions [7].…”
Section: Introductionsupporting
confidence: 87%
“…It has been reported that the total incidence of both groups of ADRs was 6.7% with an overall fatality rate of 0.32%; of which the incidence of ADRs responsible for hospital admission was 4.7% and 2.0% occurred in in-patients. 4,5 ADRs are ranked between the fourth and sixth as leading causes of death in the USA. [5] ADRs are reported to be the seventh most common cause of death in Sweden.…”
Section: Introductionmentioning
confidence: 99%
“…3,14,19 Nurses constitute a potentially valuable source for voluntary ADR reports in hospitals where ADR is more likely to be severe. 19 If nurses are actively involved in pharmacovigilance, ADRs in hospitals can be detected early and reported more accurately.…”
Section: Introductionmentioning
confidence: 99%